Early colonial Virginia and slavery - Prax, Ivo (2007)
The thesis examines the beginnings of the Jamestown settlement and the process of enslavement of the Africans. It explores difficulties which beset the settlement right form the beginning. Among these are the initial inability to grow food, the shortage of workers and the dubious characters of newcomers. The second part is devoted to blacks. It comments on whites' negative attitude towards blacks, the status of first blacks who came in 1619 and the view of law and courts on blacks.